2018
DOI: 10.18552/joaw.v8i1.429
|View full text |Cite
|
Sign up to set email alerts
|

Affective Language in Student Peer Reviews: Exploring Data from Three Institutional Contexts

Abstract: Although peer review is a common practice in writing classrooms, there are still few studies that analyze written patterns in students' peer reviews across multiple institutional contexts. Based on a sample of approximately 50,000 peer reviews written by students at the University of South Florida (USF), Malmö University (MAU), and the University of Tartu (UT), this study examines how students formulate criticism and praise, negotiate power relations, and express authority and expertise in reviewing their peer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…The discourse of peer review has been examined in various ways such as reviewers' use of direct intervention, suggestions, commands, criticisms, hedging, or encouragement (Kourilova, 1998;Wärnsby et al, 2018). Three salient points which emerged from the content analysis of peer-review comments were the consistency in feedback pattern, affective language, and students' professionalism.…”
Section: Qualitative Analysis Of the Discourse Of Peer Reviewmentioning
confidence: 99%
“…The discourse of peer review has been examined in various ways such as reviewers' use of direct intervention, suggestions, commands, criticisms, hedging, or encouragement (Kourilova, 1998;Wärnsby et al, 2018). Three salient points which emerged from the content analysis of peer-review comments were the consistency in feedback pattern, affective language, and students' professionalism.…”
Section: Qualitative Analysis Of the Discourse Of Peer Reviewmentioning
confidence: 99%
“…Researchers have noted that receiving feedback from a peer, particularly in a faceto-face environment, can be threatening for students (Warschauer, 2002). One way some instructors limit this concern is by conducting the peer review process in an online environment (Wärnsby, Kauppinen, Aull, Leijen, & Moxley, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers have noted that receiving feedback from a peer, particularly in a faceto-face environment, can be threatening for students (Warschauer, 2002). One way some instructors limit this concern is by conducting the peer review process in an online environment (Wärnsby, Kauppinen, Aull, Leijen, & Moxley, 2018). A study by Wärnsby et al (2018) analyzed the emotionally-laden language that students provide in an online setting when giving feedback to their peers and found that students tend to provide more positive than negative responses to their peers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Como es sabido, los artículos de investigación, antes de ser aceptados por una revista, pasan un proceso de revisión, y lo mismo cabe decir para los PNTs, en cuya primera página aparece el nombre y firma no sólo de quien lo ha elaborado, sino también de las personas que lo han revisado y que han autorizado su uso (Compañó y Ríos, 2010). Las actividades de revisión entre pares de productos escritos en las clases de ciencias han recibido atención en diversas investigaciones, mostrándose en general resultados positivos en su implementación (Nelson y Schunn, 2009); estos resultados positivos, pueden, encima, mejorarse más si los estudiantes reciben formación acerca de cómo realizar la revisión entre pares (Wärnsby et al, 2018). Además, la mejora de la escritura debida a las revisiones es mayor si los estudiantes no solo reciben información sobre sus productos escritos, sino si también elaboran revisiones sobre los productos de sus compañeros (Cho y Macarthur, 2011).…”
Section: Introducción Y Estado De La Cuestiónunclassified